Metafisika dalam Pandangan Advaita Vedanta dan Dvaita Vedanta (Diskursus Monistik Śańkarācārya dan Dualistik Madhvācārya) - Siswadi, Gede Agus; Murtiningsih, Rr Siti (Sophia Dharma: Jurnal Filsafat, Agama Hindu, dan Masyarakat, 2023)
Metaphysics in philosophical thought is considered as "fundamental philosophy" as well as "the basis of philosophy". Efforts to reveal about "being", "the way of being" is part of metaphysics. There is an interesting debate between the dvaita vedānta (Śańkarācārya) with the monistic concept and the dvaita Vedānta of the Madhvācārya and its dualistic concept. The results of this study are 1). Śańkarācārya recognizes only one reality namely Brahman, apart from that it is unreal, even according to Śańkarācārya this world is unreal. The real world is the influence of the maya. Jiva is identical with Brahman, and the ultimate reality is Brahman. 2) Madhvācarya put forward the dvaita theory by explaining everything in pairs, according to Madhvācārya God is different from Jiva, Jiva is different from one another, God is different from thing, Jiva is different from thing and one thing is different from other things.